Serial changes in regional cerebral blood flow in Gerstmann–Sträussler–Scheinker disease caused by a Pro-to-Leu mutation at codon 105 in the prion protein gene - Honami Kawai; Taiki Matsubayashi; Takanori Yokota; Nobuo Sanjo (Prion, 2023)
ABSTRACTGerstmann–Sträussler–Scheinker disease with a Pro-to-Leu substitution at codon 105 in the prion protein gene (GSS-P105L) is a rare variant of human genetic prion disease. Herein, we report the case of a patient with GSS-P105L, who showed serial changes in regional cerebral blood flow (rCBF) on single-photon emission computed tomography (SPECT). A 42-year-old woman, with an affected father presenting with similar symptoms, had a 1-year history of progressive gait disturbance, lower-limb spasticity, and psychiatric symptoms. Genetic analysis confirmed the diagnosis of GSS-P105L. Eleven months after disease onset, brain magnetic resonance imaging (MRI) showed bilateral frontal lobe-dominant cerebral atrophy without hyperintensity on diffusion-weighted imaging (DWI) sequences; meanwhile, SPECT revealed non-specific mild hypoperfusion. Follow-up MRI at 52 months after onset demonstrated progressive frontal lobe-dominant cerebral atrophy without hyperintensity on DWI, while SPECT revealed a marked decrease in rCBF in the bilateral right-dominant frontal lobe. Patients with GSS with a Pro-to-Leu substitution at codon 102 (GSS-P102L) have been reported to exhibit hyperintensity on DWI-MRI and a diffuse decrease in CBF with a mosaic-like pattern on SPECT, which is absent in patients with GSS-P105L, thereby possibly reflecting the differences in pathophysiology between GSS-P102L and GSS-P105L.